Executive Functions in Predicting Weight Loss and Obesity Indicators: A Meta-Analysis - Du, Zhongquan; Li, Jingjing; Huang, Jiaai; Ma, Jing; Xu, Xiaoyu; Zou, Rong; Xu, Xia (Frontiers in Psychology, 2021)
While previous studies have suggested that there exists a relationship between obesity and executive function (EF), the mechanisms and causal relationship between them remain unknown. There are important clinical implications of determining whether EF can predict and treat obesity. We conducted a multilevel meta-analysis of randomized controlled trials (RCTs) and longitudinal studies. Specifically, we investigate a) whether EF interventions have an effect on weight loss, b) whether baseline EF can be a predictor of future weight loss through obesity treatment, and c) whether early life EF can predict future weight change. Eight RCTs and 17 longitudinal studies with a total of 11393 participants were identified. We found that a) EF interventions may not have an effect on weight loss, b) baseline inhibition and delay discounting significantly predict future weight loss through obesity treatment, c) age plays a moderating role in the relationship between working memory and weight loss through intervention, and d) early life inhibition significantly predicts future weight change. Our results seem to support the assumption that the relationship between EF and obesity is not direct, and a higher-order factor, such as genes, may link obesity and EF. RCTs and longitudinal studies with great power are needed to confirm/refute these findings.